Oracle SOA suite 11g administrator's handbook : create a reliable, secure, and flexible environment for your Oracle SOA suite11g Service infrastructure and SOA composite applications /: create a reliable, secure, and flexible environment for your Oracle SOA suite11g Service infrastructure and SOA composite applications. (2012) - Aboulnaga, Ahmed; Pareek, Arun
No abstract available